Coexistence of the city with its rivers: study of the riverside landscape in Teresina, Piauí, Brazil (Research, Society and Development, 2020)
Population growth and the disordered urbanization process directly affect rivers and their banks, causing negative effects, such as the destruction of riparian forest, problems related to public health, increased flood risks, in addition to affecting physical and visual. Thus, this study aims to analyze the different riverside landscapes between the Juscelino Kubitschek and João Isidoro França bridges, in the city of Teresina, Piauí, Brazil. For landscape analysis, visits were made in loco, photographic record, survey of aerial photographs and satellite images, cartographic maps, collected at the City Hall of Teresina and on the internet, as well as analysis of the local relations of the urban structure, through urban covers and their overlays. In view of the analyzes carried out, it was possible to perceive the relationship of five riverside neighborhoods in the city of Teresina. The east side of the Poti River presents occupation represented by the highest income class, the greatest diversity of uses concentrated in commercial activities and a large amount of empty land, which can be configured as an action of real estate speculation. The west side of the Poti River also presents a diversity of activities, concentrated on institutional uses. In both cases, the Riberinho parks are still poorly structured. Thus, the importance of incorporating nature and environmental issues in urban guidelines is emphasized, since the insertion of green areas in the context of large cities can contribute to a re-urbanization, even on a smaller scale.